A Method to Quantitatively Assess Dermal Exposure to Volatile Organic Compounds. Issue 8 (29th July 2017) - Creta, Matteo; Poels, Katrien; Thoelen, Laurens; Vranckx, Karine; Collaerts, Peter; Jansen, Fleur; Vangeel, Michel; Godderis, Lode; Duca, Radu-Corneliu; Vanoirbeek, Jeroen A.J
Abstract: Assessing dermal exposure of workers to noxious chemicals becomes increasingly important in industrial settings. Among various chemicals, volatile organic compounds (VOCs) are widely used in industrialized countries, but still there are no validated methodologies able to accurately quantify skin exposure. In this study, we developed a sensitive methodology based on activated charcoal cloth (ACC) to quantitatively assess skin exposure to 181 VOCs. The majority of the VOCs (156) showed a constant desorption efficiency (DE) of ~100% over the studied concentration range. Seven VOCs showed a concentration dependency for the DEs, which we described by a Dubinin–Raduskevich desorption isotherm. For 18 compounds, the DEs were situated below 80% but showed to be constant over the concentration range. All tested VOCs showed a good storage stability on ACC, especially at −80°C storage. Only for n-pentane there was a decrease of ~40% when it was stored for a month. In a controlled environment test, ACC has shown to reflect well the increasing concentrations of VOCs in the air with a high linearity ( R 2 ≥ 0.812, except for gamma-butyrolactone where R 2 = 0.570). In this study, we show that ACC is a suitable sampling material for quantitatively assessing dermal exposure to 181 VOCs in terms of sensitivity and DE. This method will allow more studies that are detailed on dermal exposure, which will lead to a better assessment of skin exposure in occupational settings.